Financial Technology as a Socio-Technical Entity in the Digital Financial System: A Systematic Literature Review - Inngamul Wafi; Slamet Pamuji; Mohammad Dendi Abdul Nasir (Institute of Advanced Knowledge and Science, 2026)
This study aims to advance FinTech scholarship by reconceptualizing financial technology as a socio-technical entity embedded within broader digital financial systems, addressing the limitations of technology-centric and efficiency-oriented approaches that dominate existing literature. The study employs a Systematic Literature Review (SLR) of peer-reviewed international articles published between 2021 and 2026. Drawing on multidisciplinary sources from information systems, finance, regulation, and socio-technical studies, the review applies a transparent and replicable selection process and thematic synthesis to identify dominant patterns, conceptual shifts, and research gaps. The findings reveal a clear conceptual transition in recent FinTech research toward integrative socio-technical analyses that emphasize the co-evolution of digital infrastructures, institutional arrangements, regulatory governance, and social practices. Platformization and datafication emerge as central dynamics reshaping market power, financial inclusion, and systemic risk. The review demonstrates that FinTech technologies generate context-dependent outcomes influenced by regulatory capacity, data governance regimes, institutional trust, and user practices. The study highlights the need for ecosystem-level approaches to FinTech governance that move beyond firm-centric regulation. Financial inclusion is shown to be a contingent socio-technical outcome rather than an automatic effect of digitalization, while systemic risk increasingly arises from platform interdependencies, data concentration, and algorithmic opacity.